(untitled) (Innovaciones Educativas, 2025)
This paper presents an innovative experience in the implementation of an astronomy project addressed to Colombian and Costa Rican primary school students, from public and private institutions, aged 8 to 11 years. The initiative stood out for its virtual approach, which enabled the encounter and collaboration between students from different countries. The project implemented didactic strategies based on STEAM education, focused on problem and project-based learning. Among the highlighted activities were included astronomical observation sessions, presentations to Costa Rican students, and the use of origami to simulate the construction of spacecraft. Through a case study, experiences and results of this educational practice from a specific context regarding the development of an Astronomy project course are shared. Results highlight the importance of problem-solving and project development to foster collaborative and experiential learning among students, which are the training’s core, while the teacher acts as a facilitator. Furthermore, the richness of knowledge and experiences arisen from the exchange between students from different cultures is highlighted, thus enhancing their educational experience.